2010
DOI: 10.1590/s0004-282x2010000100022
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of symptoms of attention deficit and hyperactivity disorder in autistic children

Abstract: Background: Both DSM-IV and the ICD-10 exclude diagnosis of attention deficit/hyperactivity disorder (ADHD) when autism diagnostic is present. Some authors suggest, however, that autism can be associated to other comorbidity amongst which the ADHD. Objective: To estimate prevalence of ADHD in children with autism. Method: Children were selected from a specialized school, all of then had previous diagnosis or diagnostic suspicion of autism. The Brazilian version of the KIDDIE-SADS PL was applied to parents for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
(59 reference statements)
0
17
0
1
Order By: Relevance
“…Psychiatric conditions that are particularly common in children with ASD include Attention-Deficit/Hyperactivity Disorder (ADHD), mood disorders, and anxiety disorders. Prevalence rates of ADHD symptoms in ASD range from 28.2-87% (Amr et al, 2012; Ames & White, 2011; Frazier et al, 2001; Ponde, Novaes, & Losapio, 2010; Sinzig, Walter, & Doepfner, 2009; Simonoff et. al., 2008); prevalence rates of mood disorders comorbid with ASD have been estimated to range from 2-57% (Amr et al, 2011; Matson & Nebel-Schwalm, 2007; Mazefsky, Folstein, & Lainhart, 2008, Whitehouse, Durkin, Jacquet, Ziatas, 2009); and prevalence rates for anxiety disorders in ASD range from 15.7-84.1% (Mannion, Leader, & Healy, 2013; Muris, Steerneman, Merckelbach, Holdrinet, & Meesters, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric conditions that are particularly common in children with ASD include Attention-Deficit/Hyperactivity Disorder (ADHD), mood disorders, and anxiety disorders. Prevalence rates of ADHD symptoms in ASD range from 28.2-87% (Amr et al, 2012; Ames & White, 2011; Frazier et al, 2001; Ponde, Novaes, & Losapio, 2010; Sinzig, Walter, & Doepfner, 2009; Simonoff et. al., 2008); prevalence rates of mood disorders comorbid with ASD have been estimated to range from 2-57% (Amr et al, 2011; Matson & Nebel-Schwalm, 2007; Mazefsky, Folstein, & Lainhart, 2008, Whitehouse, Durkin, Jacquet, Ziatas, 2009); and prevalence rates for anxiety disorders in ASD range from 15.7-84.1% (Mannion, Leader, & Healy, 2013; Muris, Steerneman, Merckelbach, Holdrinet, & Meesters, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual of Mental Disor ders, 4 th Edition (DSMIV), the PDD group has five diffe rent cate gories: autistic disorder, Rett's disorder, childhood di sintegrative disorder, Asperger syndrome and pervasive de ve lopmental disorder -not otherwise specified (PDDNOS) 1 . Associated symptoms such as hyperactivity 2 , aggressi veness, epilepsy and insomnia are common and aggravate the clinical condition, which in some cases may require pharmacological management 3 . Bearing in mind that the neurobiological origin of PDDs remains to be fully clarified, there are no specific diagnostic markers of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…139,140 In addition, low concentrations of omega-3 fatty acids have been observed in the plasma phospholipids and erythrocytes of subjects with ADHD, 108 a neurodevelopmental disorder with clinical presentation and genetic biomarkers comparable to that of autism. [141][142][143] Children with autism have been shown to have 20% lower omega-3 fatty acid plasma concentrations compared with mentally retarded controls. 144 The same trial reported no significant difference in the omega-6 fatty acid concentrations, which resulted in a significant increase in the omega-6:omega-3 ratio in the group with autism.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%